2018
DOI: 10.11118/actaun201866010069
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionally Desirable Fatty Acids Including Cla of Cow's Milk Fat Explained by Animal and Feed Factors

Abstract: This study evaluated the effects of four factors (breed, parity, month of lactation and feeding ration) on the total explained variation (R 2 ) determining composition of nutritionally important fatty acids. Individual milk samples were collected four times over an entire year (March, June, September, and December, respectively) on a conventional farm from two breeds: Czech Fleckvieh (dual-purpose, local) and Holstein (dairy, worldwide). In total, 145 samples (36; 38; 35 and 36, respectively) were analysed. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Three FAs that are referred to as HFA [ 114 ] are lowest at the start of lactation but increase as lactation progresses. By contrast, the proportions of C18:1 c 9 and LA, which are considered to have cardioprotective effects, are present in higher amounts early in lactation [ 16 , 81 ]. RA is another FA with health benefits [ 115 ].…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Three FAs that are referred to as HFA [ 114 ] are lowest at the start of lactation but increase as lactation progresses. By contrast, the proportions of C18:1 c 9 and LA, which are considered to have cardioprotective effects, are present in higher amounts early in lactation [ 16 , 81 ]. RA is another FA with health benefits [ 115 ].…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
“…Some factors affecting the FA profile of milk (such as altitude, breed, lactation order (parity), lactation stage (days in milk), and diet) have been described previously [ 8 , 9 , 10 , 11 , 12 , 13 ]; nevertheless, these factors continue to be studied because of their wide-range of variation and their large number of possible mutually combined effects. In some studies using multifactorial datasets, the main factors affecting milk FA composition were feeding ration, herd, cow´s individuality, and lactation stage; whereas, breed and parity showed only small effects [ 10 , 14 , 15 , 16 , 17 ]. Although animal factors evidently affect the FA profile of milk fat [ 18 ], the main factors are related to dairy cow nutrition [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transfer efficiency is the term used to refer to the amount of fatty acids that can be transferred from dietary fat. Many studies illustrated that the transfer efficiency ranges from 2% to 4% for eicosapentaenoic acid (EPA) which is lower than docosapentaenoic acid (DHA) [ 32 ]. It was found that feeding fish oil in a rumen-protected manner increases transfer efficiency.…”
Section: Designing Functional Foodmentioning
confidence: 99%
“…Fish oil at recommended level in dairy diet seems to increase milk LA compared to vegetable oils. Combination of both fish and vegetable oils enrich with LA has the potential effect to increase milk LA level like soybean and sunflower [ 32 , 38 ]. Yu and Hu [ 39 ] found that, when cereals were substituted with lupin seeds, there was an improvement in milk production and higher concentration of milk protein and fat.…”
Section: Designing Functional Foodmentioning
confidence: 99%